PENGARUH KEHADIRAN KOMISARIS INDEPENDEN, KOMITE AUDIT, DAN KOMITE PEMANTAU RISIKO TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA PERIODE 2018-2022 - Paputungan, Sharon Voice Thiffania; Tulung, Joy Elly; Untu, Victoria N. (FEB Universitas Sam Ratulangi Manado, 2023)
This research aims to examine the influence of the presence of independent commissioners, audit committees and risk monitoring committees oln financial performance. The population of this research is all banks registered with the Financial Services Authority which are domicied in the country. The sampling technique used was purposive sampling and a sample of 71 banks was obtained in accordance with the specified criteria. The data anaysis method used is Panel Data Regression Analysis with a Random Effect Model approach. The research results show that, in particular, the presence of Independent Commissioners does not have a significant elffect on Financial Performance. The Audit Committee does not have a significant effect on Financial Performance. And the Risk Monitoring Committee does not have a significant effect on Financial Performance. Simultaneous, the presence of Independent Commissioners, Audit Committees and Risk Monitoring Committees does not have a significant effect on banking financial performance in Indonesia for the 2018-2022 period.